(untitled) (JURNAL IBU DAN ANAK, 2025)
Back pain is one of inconvenience on quarter III pregnant women which can disturb daily activity. Based on the researcher’s preliminary survey in January 2022 at PMB Dince Safrina Pekanbaru City, out of 10 quarter III pregnant women found 8 people of them complaint of back pain. One of nonpharmacologist method to overcome back pain is through Back Massage. The purpose of this research was to find out the influence of back massage on back pain of quarter III pregnant women. The type of this research was pre experiment with one group pretest and post test design. The population in this research were quarter III pregnant women who checked their pregnancy at PMB Dince Safrina Pekanbaru City in Januari-April 2022. The samples in this research were 15 quarter III pregnant women with back pain complaint selected through purposive sampling. Data collection method was observation by using data collection instrument namely Numeric Rating Scale (NRS). The test used was Wilcoxon test with significance level 95%. Based on the statistical test, there was influence of back massage on back pain of quarter III pregnant women (p = 0,001). It is expected that the medical staff especially midwifery at PMB Dince Safrina to be able to apply back massage as one of nonpharmacology therapy on managing back pain of quarter III pregnant women